2004
DOI: 10.1177/0115426504019002184
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia as a Predictor of Mortality in Hospitalized Elderly Patients

Abstract: Background: Hypoglycemia during hospitalization occurs in patients with and without diabetes. The aims of this study were to determine the incidence, associated risk factors, and short-and long-term outcome of hypoglycemia among hospitalized elderly patients. Methods: This is a case-control study conducted at geriatric and medicine departments. All patients 70 years or older with documented hypoglycemia hospitalized within 1 year (n ϭ 281) were compared with a nonhypoglycemic group of 281 elderly, randomly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 21 publications
(39 reference statements)
4
43
0
1
Order By: Relevance
“…Risk factors for hypoglycemia in hospitalized elderly patients include sepsis, hypoalbuminemia, malignancy, female gender, elevated serum creatinine, hepatic dysfunction, and therapy with glucose lowering medications. 9 Of these, hypoalbumenia and therapy with a glucose lowering medication were present in our patient. Our patient had recently started glyburide for treatment of steroid-induced hyperglycemia and received 3 days of therapy without an episode of hypoglycemia.…”
Section: Discussionmentioning
confidence: 59%
“…Risk factors for hypoglycemia in hospitalized elderly patients include sepsis, hypoalbuminemia, malignancy, female gender, elevated serum creatinine, hepatic dysfunction, and therapy with glucose lowering medications. 9 Of these, hypoalbumenia and therapy with a glucose lowering medication were present in our patient. Our patient had recently started glyburide for treatment of steroid-induced hyperglycemia and received 3 days of therapy without an episode of hypoglycemia.…”
Section: Discussionmentioning
confidence: 59%
“…[15][16][17] Higher mortality rates have also been reported in patients presenting to ER with seizures, intoxication, breathlessness, malignancy, sepsis, hypoglycemia, and hyperglycemia. [18][19][20][21] Increasing leukocyte count, even within the normal range, has been associated with increased mortality. 22,23 Hyponatremia at presentation has a complicated relationship with the risk of in-hospital mortality and it has been shown that early resolution attenuates the increased risk it presents.…”
Section: Social and Clinical Profile Of Patientsmentioning
confidence: 99%
“…7 Thus, for the elderly and other at-risk patients with a recent history of hypoglycemia, routine finger stick glucose testing may be appropriate even in endof-life care to minimize these barriers and prevent uncomfortable symptoms of hypoglycemia, especially if the patient is in a care setting that would easily allow testing and death is not imminent. Regardless, it is imperative that clinicians caring for terminally ill patients be aware of the signs of hypoglycemia in the absence of diagnostic testing so that appropriate care discussions and clinical decision making occur between clinicians and the patient's surrogate.…”
Section: Barriers To Recognizing Hypoglycemia At the End Of Lifementioning
confidence: 99%